Pitfalls in Implementing the EU Whistleblower Directive - Scheu Harald Christian (Wroclaw Review of Law, Administration and Economics)
In this paper, we focus on two conceptual problems associated with the EU Whistleblower Directive and point out issues that may undermine or even frustrate the successful implementation of the Directive in a national context. While fully acknowledging strong arguments for, and undeniable benefits of, speaking in favour of EU whistleblower protection, it has to be noted that a specific form of forced gold-plating calling for the extension of the material scope of protection may complicate the interpretation of the autonomous part of legislation and lead to legal insecurity. Moreover, new elements of whistleblower protection as introduced by the Directive diverge from the case law of the European Court of Human Rights. The introduction of higher standards of protection in favour of whistleblowers does not raise problems in relations between the state and the individual, but some EU rules may cause problems in horizontal relations between private individuals, since fair balancing of interests as required by Strasbourg jurisprudence may be not always guaranteed.